2017
DOI: 10.1371/journal.pone.0178421
|View full text |Cite
|
Sign up to set email alerts
|

Feeding toxicity and impact of imidacloprid formulation and mixtures with six representative pesticides at residue concentrations on honey bee physiology (Apis mellifera)

Abstract: Imidacloprid is the most widely used insecticide in agriculture. In this study, we used feeding methods to simulate in-hive exposures of formulated imidacloprid (Advise® 2FL) alone and mixtures with six representative pesticides for different classes. Advise, fed at 4.3 mg/L (equal to maximal residue detection of 912 ppb active ingredient [a.i.] in pollen) induced 36% mortality and 56% feeding suppression after 2-week feeding. Treatments with individual Bracket (acephate), Karate (λ-cyhalothrin), Vydate (oxamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 63 publications
8
78
3
1
Order By: Relevance
“…After weekly treatment for three weeks, honeybees treated with 552 mg/L Advise (imidacloprid) showed significantly higher AChE activity than water‐only control, while other concentrations maintained similar AChE activity to that of control. These data confirmed our previous findings (Zhu et al, ) that also showed no significant change in AChE activity after both feeding treatment and spray treatment with imidacloprid formulation. But, the AChE activity was induced in bees treated with higher concentrations of imidacloprid in this study.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…After weekly treatment for three weeks, honeybees treated with 552 mg/L Advise (imidacloprid) showed significantly higher AChE activity than water‐only control, while other concentrations maintained similar AChE activity to that of control. These data confirmed our previous findings (Zhu et al, ) that also showed no significant change in AChE activity after both feeding treatment and spray treatment with imidacloprid formulation. But, the AChE activity was induced in bees treated with higher concentrations of imidacloprid in this study.…”
Section: Resultssupporting
confidence: 93%
“…These data confirmed our previous findings (Zhu et al, 2017a(Zhu et al, , 2017b ) that also showed no significant change in AChE activity after both feeding treatment and spray treatment with imidacloprid formulation. But, the AChE activity was induced in bees treated with higher concentrations of imidacloprid in this study.…”
Section: Influence On Acetylcholinesterase Activitysupporting
confidence: 92%
See 3 more Smart Citations